Expansão da educação secundária em Pernambuco atores políticos e a interiorização dos ginásios públicos (1948-1963) - Santos, Kalline Laira Lima dos (Editora Oficina Universitária, 2022)
This book is the result of several meetings. The first of them was on the floor of my school, during High School, where I heard, for the first time, that it was possible for students from Public Schools to enter Higher Education. Therefore, History was the path, the choice. In this path, I carry the commitment to history and education, which constitutes a field of research crossed by theoretical, personal, collective experiences and social principles. In order to understand and interpret events and stories about secondary schools in Pernambuco, particularly their social pressure to increase vacancies in public gymnasiums, I point out the following questions in this book: How did the expansion process of the first cycle of public secondary education occur in Pernambuco? How did state, municipal and federal political actors act in the creation of these educational establishments? What were the financing policies for the creation of these gyms? As Marc Bloch (1997, p. 17) says: "Isn't it true that, in order to act wisely, it is necessary, first, to understand?". Thus, this book seeks to understand the role of the State in the process of democratization of schooling in Pernambuco society.